GPR158 in pyramidal neurons mediates social novelty behavior via modulating synaptic transmission in male mice - Wei, Shoupeng; Jiang, Jian; Wang, Dilong; Chang, Jinlong; Tian, Liusuyan; Yang, Xiuyan; Ma, Xiao-Ru; Zhao, Jing-Wei; Li, Yiming; Chang, Shuwen; Chi, Xinjin; Li, Huiliang; et al. (Cell reports (Cambridge), 2024)
Impairment in social communication skills is a hallmark feature of autism spectrum disorder (ASD). The role of G-protein-coupled receptor 158 (GPR158) in ASD remains largely unexplored. In this study, we observed that both constitutive and cell-/tissue-specific knockouts of Gpr158 in pyramidal neurons or the medial prefrontal cortex (mPFC) result in impaired novelty preference, while sociability remains unaffected in male mice. Notably, the loss of GPR158 leads to a significant decline in excitatory synaptic transmission, characterized by a reduction in glutamate vesicles, as well as the expression and phosphorylation of GluN2B in the mPFC. We successfully rescue the phenotype of social novelty deficits either by reintroducing GPR158 in the mPFC of Gpr158 deficient mice or by chemogenetic activation of pyramidal neurons where Gpr158 is specifically ablated. Our findings indicate that GPR158 in pyramidal neurons plays a specific role in modulating social novelty and may represent a potential target for treating social disorders. [Display omitted] •GPR158 deletion results in sex-specific deficits of social novelty in male mice•GPR158 deletion leads to decreased excitatory synaptic transmission in the mPFC•Social novelty deficits can be rescued by reintroducing GPR158 in the mPFC or chemogenetics Wei et al. report that global and cell-specific knockouts of Gpr158 result in impairment of social novelty preference in male mice, characterized by inhibited excitatory synaptic transmission in the mPFC. The phenotype of social novelty deficits can be rescued by GPR158 re-expression and chemogenetic modulation.